Prediction of tire friction - Muhammad Muhaimin, Shaari (2009)
Automotive industry was moving ahead to be an important industry in Malaysia and in the world. Tire is one of the main parts in the car which is always costly. In recent years, much progress has been made in the physical understanding and modelling of the friction behaviour of elastomers at rough and fine surfaces. The friction between the tires of the automobile and the road determine your maximum acceleration, and more importantly the minimum stopping distance. So the nature of that friction could actually be a matter of life and death. The main objective of the project is to determine the friction coefficient of the tyre by using the Algor software. In the beginning of the project, the information about friction, tyre, and the suitable software are gather. Then, the tyre model and the surfaces that represent the road surface condition are draw by using the Solidwork software, and then the model is transferred to the Algor software to run the simulation. From the simulation, the result show that the friction coefficient is about 0.37 to 0.61.from the case study result, this result is approximate to the real value of the coefficient of static friction.